2021
DOI: 10.1186/s40814-021-00798-z
|View full text |Cite
|
Sign up to set email alerts
|

Cluster randomised controlled feasibility study of HENRY: a community-based intervention aimed at reducing obesity rates in preschool children

Abstract: Background Community-based obesity prevention interventions are often commissioned despite the limited evidence base. HENRY (Health, Exercise, Nutrition for the Really Young) is a programme delivered to parents of preschool children across the UK. Early evidence suggests that it may be effective, but a robust evaluation has not been conducted. We initiated a systematic evaluation of HENRY by studying the feasibility of conducting a multi-centre definitive trial to evaluate its effectiveness and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 53 publications
(44 reference statements)
0
12
0
Order By: Relevance
“…After full‐text screening, an additional 37 studies were identified. These included 20 studies 5,70–88 reporting 12 additional interventions and 17 studies 89–105 reporting outcomes from the interventions included in the review by Karacabeyli et al but those published after July 2017. The search of the clinical trial registries, the gray literature, and reference lists of included studies identified an additional 32 studies for inclusion in our review (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…After full‐text screening, an additional 37 studies were identified. These included 20 studies 5,70–88 reporting 12 additional interventions and 17 studies 89–105 reporting outcomes from the interventions included in the review by Karacabeyli et al but those published after July 2017. The search of the clinical trial registries, the gray literature, and reference lists of included studies identified an additional 32 studies for inclusion in our review (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…The priority placed on the delivery of HENRY programmes or similar may be influenced by stakeholder perceptions of whether the programme can demonstrate an effect [ 62 ], but these data are rarely available for public health obesity prevention programmes delivered at scale. In this study, we applied a novel approach to evidence generation through the conduct of a comprehensive early-phase (evidentiary) intervention enhancement and evaluation [ 13 ] prior to testing the feasibility of assessing the effectiveness of HENRY [ 15 ]. This is in contrast to conventional implementation research, which would usually be conducted following definitive randomised evaluations to determine clinical effectiveness (in this case, childhood obesity prevention).…”
Section: Discussionmentioning
confidence: 99%
“…We developed and evaluated an intervention to optimise the implementation of an existing pre-school obesity prevention group programme, HENRY (Health, Exercise, Nutrition for the Really Young), prior to assessing the feasibility of undertaking a randomised controlled trial of its effectiveness in work which has been previously been published [ 14 , 15 ]. HENRY is an 8-week programme delivered to groups of parents of preschool children.…”
Section: Introductionmentioning
confidence: 99%
“…Out of the 217 international studies, five studies (six trials) were conducted in the UK and were included in the final review. [34][35][36][37][38] One study was conducted in Lancashire, 34 one in Glasgow, 35 one in two areas in North and Central…”
Section: Description Of the Studiesmentioning
confidence: 99%
“…The four preventative trials include the Be active, Eat healthy/Healthy Heroes 34 intervention, the ToyBox 35 intervention, the Health Exercise Nutrition for the Really Young (HENRY) 36 programme, and the Planet Munch programme, trial 2. 38 Three out of four trials (Be Active, Eat healthy/Healthy Heroes, ToyBox, HENRY) focused on disadvantaged families or deprived areas.…”
Section: Preventative Interventionsmentioning
confidence: 99%